Une exposition au musée du Louvre "Musées nationaux, Nouvelles acquisitions, 2 septembre 1939 - 2 septembre 1945" = An exhibition at the Louvre Museum : "Musées nationaux, Nouvelles acquisitions, 2 september 1939 - 2 september 1945" - Polack, Emmanuelle (2022)
An exhibition at the Louvre Museum: "Musées Nationaux, Nouvelles acquisitions, 2 September 1939-2 September 1945" In 1945-46, the exhibition "Musées Nationaux - Nouvelles Acquisitions, 2 septembre 1939- 2 septembre 1945" showed new acquisitions of French national museums between September 2nd, 1939 and September 2nd, 1945. Today, we are confronted with the delicate but fundamental question of the provenance of the selected works: How was it possible to accumulate so much wealth in these destructive times, which were marked by German raids and «Aryanizations»? This article aims to answer this very question. Visitors to the exhibition were able to admire numerous purchases as well as works that were the result of bequests and donations. But at the same time, they were likely amazed at what could be acquired under not only occupation but also more than difficult working conditions, under which the national cultural assets had to be both defended and enriched. The exhibition shown at the Musée du Louvre testified to the fact that the scientific staff of the national museums, in the darkest hours, successfully fulfilled the double task of saving public collections and increasing national cultural heritage. To demonstrate this, all the departments of the Louvre, as well as the Musée d’Art moderne, the Musée Guimet, the Musée des Arts et Traditions populaires, the Musée des Antiquités nationales, the palace museums of Versailles, Compiègne and Malmaison, and museums in the regions, were invited to select their distinctive pieces acquired during the war, including from bequests and donations. The exhibition ended on February 6th, 1946 without any mention of the provenance of the works acquired between 1939 and 1945.
Keywords: Geschichte 1939-1946; Kunstraub; Erwerbung; Museum; Frankreich